The 'Barn Door Closing Effect': application to the Portuguese mutual fund industry - Samuel Ferreira Correia (2018)
Behavioural finance is nowadays one of the most interesting themes in finance, once the way investors think is affecting the world's transactions in financial markets. "Barn Door closing" is a phenomenon that consists in undertaking a behaviour in the future that would have been profitable in the past. There are several reasons underlying this phenomenon, as, for example, the uncertainty about the outcomes of financial markets. Some investors need to see a good performance of a mutual fund, measured by return, to invest. This will create a kind of "delay" in the investment because the investor will only earn money in the next period instead of earn it in the past. Being the first time that this thematic is applied to European mutual funds, namely the Portuguese ones, we run a regression over a panel of 29 mutual funds from 2008 to 2012, to know if there is evidence of the phenomenon in the Portuguese market. Also, as we consider a period that comprises two different financial situations, one of pre-crisis and another of crisis, we run other regression with multiplicative dummies that interact with the explanatory variables, to know if the magnitude of the phenomenon is different in these two sub-periods. We find out, in the overall period regression, evidence of the phenomenon in these type of mutual funds, despite of its low magnitude. This happens because the coefficient of the variable return is approximately zero. Concerning the impact of "barn door closing" in the two sub-periods, we conclude that there is no difference in its magnitude, because the variable that interacts with lagged return has no statistical significance. Investors' performance is jeopardized. They can have higher profits by investing in the previous period instead of doing it in the following.